STRATEGI PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PERENCANAAN PROGRAM DESA PINTAR - Rudy Fadrial, Meyzi Heriyanto, Noor Efni Salam (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Strategy for Utilizing Information and Communication Technology in SmartVillage Program Planning. This research is qualitative research. The aim of the study was todetermine the strategy of technology and communication utilization in the smart village programin Rokan Hulu Regency. The research informants were the Head of Office, Head of Department,Head of Office, Office of Communication and Information, Head of Village, Village Head,Community and Youth Leaders. Data collection techniques are interviews, observation anddocumentation. Data analysis through processes ranging from data reduction, data presentation,and conclusion drawing. The results of the study show that the development and governancestrategy of Information and Communication Technology conducted by the Government of RokanHulu Regency cannot be optimally implemented.